2011
DOI: 10.2320/matertrans.l-m2011815
|View full text |Cite
|
Sign up to set email alerts
|

Slip Deformation Analysis Based on Full Constraints Model for α-Titanium Alloy at Low Temperature

Abstract: The effects of restricted slip conditions on both the Taylor factor and plastic work rate under the condition of tensile yielding have been analyzed in -titanium alloys at low temperatures, using the full constraints model. The role of secondary slip systems, i.e., the hai basal slip and hc þ ai pyramidal slip, was clarified, when the hai prismatic slip was dominant. Although no influence of secondary slip conditions on the Taylor factor was detected, the plastic work rate was sensitive to the operating second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…For titanium, M T was taken to be 2.5 according to Ref. [18]. Compression of titanium reduced one dimension of the sample by 20%, corresponding to an applied stress of 582 MPa [11].…”
Section: Simulation Parametersmentioning
confidence: 99%
“…For titanium, M T was taken to be 2.5 according to Ref. [18]. Compression of titanium reduced one dimension of the sample by 20%, corresponding to an applied stress of 582 MPa [11].…”
Section: Simulation Parametersmentioning
confidence: 99%
“…3) Slip deformation analysis based on full constraints model by Taylor theory was suggested that internal stress in α grain was developed on the normal to (0001) and hardly relaxed. 7) The accumulated tensile stress along [0001] may be responsible for initial microcracking and its opening in the hard grain. Not only the microstructure and α grain size but also texture or macrozone (microtexture), therefore, strongly affect the subsurface fatigue crack initiation.…”
Section: (Received On November 14 2017; Accepted On March 27 2018)mentioning
confidence: 99%
“…The subsurface fatigue crack generation in titanium alloys (hcp) and austenitic steels (fcc), which has been commonly reported in high-cycle regime and at low temperature, [2,3] is closely related with heterogeneous deformation due to the restriction of slip systems. [4,5] Si addition in steel causes the restriction to {110} <111> primary slips, especially over 3.8 mass% Si content at room temperature. [6] The deformation and fatigue fracture behavior in Si steels depend on their Si content and are highly reflected on their crystal orientation and microstructure.…”
Section: Introductionmentioning
confidence: 99%